Vestibular Assessments in Children With Global Developmental Delay: An Exploratory Study. Issue 2 (2016) - Dannenbaum, Elizabeth; Horne, Victoria; Malik, Farwa; Villeneuve, Myriam; Salvo, Lora; Chilingaryan, Gevorg; Lamontagne, Anouk
Abstract : Purpose: To compare results of 3 clinical vestibular tests between children with global developmental delay (GDD) and children with typical development (TD) and investigate the test-retest reliability. Methods: Twenty children with GDD (aged 4.1-12.1 years) and 11 age-matched controls with TD participated. Participants with GDD underwent 2 sessions of testing. Each session consisted of the Clinical Test of Sensory Interaction and Balance (CTSIB), Dynamic Visual Acuity (DVA) test, and the modified Emory Clinical Vestibular Chair Test (m-ECVCT). Results: Up to 33% of the children with GDD had abnormal DVA scores. m-ECVCT results of children with GDD demonstrated larger variance than children with TD. The CTSIB score was significantly reduced in the group with GDD. The test-retest reliability varied, with good reliability for the m-ECVCT and CTSIB, and fair reliability for the DVA. Conclusions: Findings suggest vestibular involvement in children in GDD. The clinical tests demonstrated moderate test-retest reliability. Abstract : The results of 3 clinical vestibular tests are compared between children with global developmental delay and children with typical development.